Tumor Necrosis Factor-α Inhibitors as a Treatment of Corneal Hemangiogenesis and Lymphangiogenesis. Issue 2 (March 2015) - Ferrari, Giulio; Bignami, Fabio; Rama, Paolo
Abstract : Abstract: The cornea is normally devoid of blood and lymphatic vessels; however, a number of infectious/inflammatory diseases can induce corneal neovascularization (CNV). Tumor necrosis factor (TNF)-α, a well known pro-inflammatory cytokine, acts on the vascular endothelium by promoting vasodilatation, edema, and leukocyte recruitment, which are all commonly associated with the development of CNV. Corneal neovascularization is the second cause of blindness worldwide; hence, pharmacological TNF-α inhibition might represent an attractive therapeutic option. Although none of the existing TNF-α antagonists has been registered as a CNV inhibitor, three of them (etanercept, adalimumab, and infliximab) have been proposed to control ocular inflammation. More specifically, it has been demonstrated that infliximab is also effective in reducing hemangiogenesis and lymphangiogenesis in different animal models of CNV. In this article, we review the role of TNF-α on the ocular surface and, in particular, its specific role in the process of CNV. Moreover, we review existing literature and speculate on the potential role of TNF-α inhibitors in the treatment of CNV.